IMPLEMENTASI STRATEGI PEMBELAJARAN AKTIF BERBASIS PEER LESSON DALAM MEMOTIVASI BELAJAR SEJARAH KEBUDAYAAN ISLAM DI MADRASAH TSANAWIYAH AL-HUDA DENDANG KABUPATEN TANJUNG JABUNG TIMUR PROVINSI JAMBI - Naini, Zainun; MY, Mahmud (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the implementation of an active learning strategy based on peer lessons in motivating students to learn Islamic Cultural History (SKI) at MTs Al-Huda Dendang, Tanjung Jabung Timur Regency, Jambi Province. The research was motivated by the low level of student participation and learning motivation in Islamic Cultural History classes, which were often dominated by conventional teaching methods. This study aimed to describe the implementation of the peer lesson strategy, identify the supporting and inhibiting factors, and explore the solutions applied to overcome the obstacles encountered during the learning process. This research employed a qualitative descriptive approach. Data were collected through observations, interviews, and documentation involving the principal, Islamic Cultural History teacher, and students of MTs Al-Huda Dendang. The data were analyzed using data reduction, data display, and conclusion drawing techniques. The findings revealed that the implementation of the peer lesson strategy successfully encouraged students to become more active, confident, and responsible in the learning process. Students were able to understand learning materials through peer interaction, which contributed to increased learning motivation and classroom participation. Supporting factors included teachers’ competence in facilitating learning activities, students’ enthusiasm, and collaborative classroom interactions. Meanwhile, inhibiting factors involved students’ difficulties in understanding materials presented by peers, limited participation among some students, and time management constraints during learning activities. The study concludes that the peer lesson strategy is an effective active learning approach for enhancing students’ motivation in learning Islamic Cultural History.